2016
DOI: 10.7717/peerj.2790
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Perceived Stress Scale (PSS): measurement invariance between athletes and non-athletes and construct validity

Abstract: BackgroundAlthough Perceived Stress Scale (PSS, Cohen, Kamarack & Mermelstein, 1983) has been validated and widely used in many domains, there is still no validation in sports by comparing athletes and non-athletes and examining related psychometric indices.PurposeThe purpose of this study was to examine the measurement invariance of PSS between athletes and non-athletes, and examine construct validity and reliability in the sports contexts. MethodsStudy 1 sampled 359 college student-athletes (males = 233; fem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 60 publications
(92 reference statements)
2
49
0
2
Order By: Relevance
“…The PSS has exhibited convergent validity and discriminant validity, with scores on the PSS having been shown to be significantly correlated with burnout, overall life stress, depression, and anxiety. [50][51][52] The instrument has also shown adequate test-retest reliability and satisfactory internal consistency, typically ranging from 0.72 to 0.86. 50,51,53 For the current study, Cronbach's α was acceptable (α = .70).…”
Section: Lonelinessmentioning
confidence: 99%
“…The PSS has exhibited convergent validity and discriminant validity, with scores on the PSS having been shown to be significantly correlated with burnout, overall life stress, depression, and anxiety. [50][51][52] The instrument has also shown adequate test-retest reliability and satisfactory internal consistency, typically ranging from 0.72 to 0.86. 50,51,53 For the current study, Cronbach's α was acceptable (α = .70).…”
Section: Lonelinessmentioning
confidence: 99%
“…Developed by Cohen et al, (1983), the PSS measure is used to assess one's perception of the degree of a given situation in life is stressful. We used a 2-factor 10-item PSS for our study (Chiu et al, 2016). Chiu et al, (2016) reported that 2-factor 10-item PSS with appropriate Manuscript to be reviewed psychometric properties.…”
Section: The Perceive Stress Scafe (Pss)mentioning
confidence: 99%
“…We used a 2-factor 10-item PSS for our study (Chiu et al, 2016). Chiu et al, (2016) reported that 2-factor 10-item PSS with appropriate Manuscript to be reviewed psychometric properties. The sample question of "perceived distress" is (e.g., how often have you felt upset because of something that happened unexpectedly?…”
Section: The Perceive Stress Scafe (Pss)mentioning
confidence: 99%
See 2 more Smart Citations